Analisis Perilaku Konsumen Generasi Z dalam Pengambilan Keputusan Pembelian Melalui Media Sosial TikTok - Ahmad Dzul Ilmi Syarifuddin; Ferri Alfadri; Ulfa Hidayati (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
This study aims to explore the consumer behavior of Generation Z in purchase decision-making through TikTok social media amidst the rapidly evolving digital economy. Employing a qualitative approach with a descriptive phenomenological design, data were collected through semi-structured in-depth interviews with 12 purposive informants aged 17–25 years who are active TikTok users and have made purchases influenced by platform content. Data analysis was conducted using Interpretative Phenomenological Analysis (IPA) to uncover the essence of informants' lived experiences. Four interrelated themes emerged: first, the influence of content creator credibility on consumer trust and purchase intention; second, the role of the For You Page (FYP) algorithm in persistently shaping consumption preferences; third, the dynamics of TikTok community social validation through comments, duets, and stitches as purchase conviction reinforcers; and fourth, emotion-driven purchase impulsivity triggered by entertainment content and live commerce features. Findings affirm that Generation Z does not form purchasing decisions through a rational-linear process, but rather through a unique, complex socio-cognitive-affective process fundamentally distinct from prior generations. Practical implications include the importance of authenticity-based creator marketing strategies, algorithm optimization, facilitation of organic user-generated content, and the ethical use of live commerce features.